PENDEKATAN PENDIDIKAN MULTIKULTURAL DALAM MEMBENTUK KARAKTER SISWA DI SEKOLAH - Fatijaroh, Ibif; Hanani, Shofiatul; Mubin, Nurul (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
The multicultural education approach in Indonesia needs to start from an early age by instilling life values ​​to form an ideal national character in the era of the industrial revolution 4.0. With the advent of fast and instant technology, local wisdom in Indonesian culture is starting to fade, as can be seen from the reduced attitudes of tolerance and empathy between citizens, which can trigger conflict and discrimination in society. Therefore, a multicultural approach is needed that can be applied to education in Indonesia, especially through educational institutions (schools) and the family environment as the main source of children's education. Multicultural education has an important role in developing student character. This education can improve students' social skills, including intercultural communication skills and an attitude of respect for diversity. Cultural diversity in Indonesia is both a strength and a challenge that needs to be preserved, so educators are needed who are professional and understand this diversity.